Pelatihan Pembuatan Alat Peraga Permainan Edukatif di TK Islam Bakti VII Jakarta - Bayu Jaya Tama; Sri Rezeki; Rahmawati Yuliyani (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Early childhood is the most important and fundamental early period in the growth and development of human life. This period is also called the golden age, many concepts and facts explain that this golden age is the time when all children's potential develops the fastest. Aspects of child development that need to be developed in early childhood include personal awareness, emotional development, building socialization, communication development, cognitive development, and motor skill development. Based on these aspects of early childhood development, a children's game media is needed to stimulate children's development and growth. One of the children's game media that can be developed is Educational Game Tools (APE). In this PKM activity, the PKM Team tries to provide training in making APE including number wheels, summing bottle caps, and sliding number boards.